PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP PERTUMBUHAN ASET PERUSAHAAN PROPERTI TERDAFTAR DI BURSA EFEK INDONESIA - Sandara, Stefen Aan; Riyanto, Wahyu Hidayat (Program Studi Ekonomi Pembangunan, 2023)
Property and real estate companies listed on the Indonesia Stock Exchange (BEI) are very popular with investors to invest in when real estate income is growing rapidly. The aim of this research is to find out what factors influence asset growth in property companies. The data analysis technique uses panel regression which combines cross section and time series data on 31 property companies listed on the Indonesia Stock Exchange (BEI) for the period 2010-2021. The research results reveal that capital structure is not significant in influencing asset growth. The profitability variable has a positive and significant effect on asset growth in property companies. When profitability rises, asset growth will increase. Meanwhile, company size has a significant negative effect on asset growth in property companies. This means that the larger the company size will actually reduce the growth of property companies.